2009
DOI: 10.1149/1.3134555
|View full text |Cite
|
Sign up to set email alerts
|

Copper Nanofilm Formation by Electrochemical ALD

Abstract: This paper describes the formation of Cu nanofilms using atomic layer deposition (ALD) via surface-limited redox replacement, also referred to as monolayer-restricted galvanic displacement. An automated flow-cell electrodeposition system was employed to make Cu nanofilms using 100, 200, and 500 ALD cycles. The cycle was composed of a sequence of steps: Pb underpotential deposition (UPD), rinsing with blank, introduction of Cu2+ at open circuit, and exchange of the Pb atoms for Cu, rinsing with a blank. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 47 publications
0
38
0
Order By: Relevance
“…The use of flow a cell was also extended to the growth of thicker Cu deposits by up to 500 SLRR cycles on Au films on glass. Interestingly enough, while the thicker films were displaying expected homogeneity and overall appearance at the end of the growth process, a flattening of the surface was reported in these experiments during the first 30 cycles [76]. The flow-cell deposition approach was also extended by Stickney et al to the growth of thinner [77] and thicker [75] Cu films on Ru substrates.…”
Section: Cu Depositionmentioning
confidence: 52%
See 1 more Smart Citation
“…The use of flow a cell was also extended to the growth of thicker Cu deposits by up to 500 SLRR cycles on Au films on glass. Interestingly enough, while the thicker films were displaying expected homogeneity and overall appearance at the end of the growth process, a flattening of the surface was reported in these experiments during the first 30 cycles [76]. The flow-cell deposition approach was also extended by Stickney et al to the growth of thinner [77] and thicker [75] Cu films on Ru substrates.…”
Section: Cu Depositionmentioning
confidence: 52%
“…Studies on the SLRR deposition of Cu on Au (111) were reported in flow-cell [36,[74][75][76][77] and in one-cell configuration [31]. In a flow-cell Stickney et al used Cu UPD to deposit the first Cu atomic layer on a Au (111) substrate, modified with an atomic layer of I atoms [36].…”
Section: Cu Depositionmentioning
confidence: 99%
“…This procedure can be extended into the area of thin film metal electrodeposition. 19,[21][22][23][47][48][49] Scale-up of this synthesis method is possible and successfully tested up to 50 grams per batch. 43 The method facilitates growing various nanoparticles architectures with controllable thickness of components in stratified structures.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Galvanic displacement, a type of electroless deposition in which the substrate or an adsorbed species acts as the reducing agent, can produce nanometer-thickness films on semiconductors and noble metals. 3,4 Galvanic deposition of copper layers has been reported on oxide-covered materials such as aluminum, tantalum, as well as TiN and TaN diffusion barriers. 5−7 However, it seems that electroless deposition and galvanic deposition have not yet been used to fabricate ultrathin films on oxidized substrates.…”
Section: ■ Introductionmentioning
confidence: 99%